2017
DOI: 10.1016/j.joca.2016.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulated circadian rhythm pathway in human osteoarthritis: NR1D1 and BMAL1 suppression alters TGF-β signaling in chondrocytes

Abstract: Objectives Circadian rhythm (CR) was identified by RNA sequencing as the most dysregulated pathway in human osteoarthritis (OA) in articular cartilage. This study examined circadian rhythmicity in cultured chondrocytes and the role of the CR genes NR1D1 and BMAL1 in regulating chondrocyte functions. Methods RNA was extracted from normal and OA-affected human knee cartilage (n=14 each). Expression levels of NR1D1 and BMAL1 mRNA and protein were assessed by quantitative PCR and immunohistochemistry. Human chon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
79
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(89 citation statements)
references
References 62 publications
(70 reference statements)
5
79
1
Order By: Relevance
“…More importantly, the phosphorylated Smad2/3 and Serpine1 expressions are also significantly reduced in Bmal1 cKO mice. While, previous reports showed that TGF-β signaling could also upregulate the Bmal1 mRNA expression in human articular cartilage 47 , whether circadian rhythm is involved in the lesions of Alk5 cKO mice needs to be studied.…”
Section: Discussionmentioning
confidence: 99%
“…More importantly, the phosphorylated Smad2/3 and Serpine1 expressions are also significantly reduced in Bmal1 cKO mice. While, previous reports showed that TGF-β signaling could also upregulate the Bmal1 mRNA expression in human articular cartilage 47 , whether circadian rhythm is involved in the lesions of Alk5 cKO mice needs to be studied.…”
Section: Discussionmentioning
confidence: 99%
“…SIRT1 was also linked to circadian rhythm by Yang et al 43 , showing that siRNAmediated knockdown or pharmacologic inhibition of SIRT1 in chondrocytes results in lower levels of transcripts for the clock gene Bmal1. It was already known that loss of Bmal1 increases cartilage damage and disrupted circadian rhythm in chondrocytes 44 , as highlighted in last year's Year in Review 45 . Interestingly, similar methods used to knock down Bmal1 expression reciprocally reduced SIRT1 expression.…”
Section: Timing Of Treatment Interventions Mattersmentioning
confidence: 99%
“…Analysis of gene expression patterns in human cartilage revealed that circadian rhythm pathways were among the most disrupted in OA patients (Akagi et al 2017, Soul et al 2018. Several studies have also demonstrated that expression of BMAL1/BMAL1 is significantly reduced in human osteoarthritic cartilage (Dudek et al 2016, Snelling et al 2016, Yang et al 2016a, Akagi et al 2017. Knockdown of BMAL1 in human chondrocytes altered TGF-β signalling and was associated with increased expression of catabolic factors (e.g.…”
Section: Links Between Dysregulation Of Circadian Rhythms and Articulmentioning
confidence: 99%
“…Knockdown of BMAL1 in human chondrocytes altered TGF-β signalling and was associated with increased expression of catabolic factors (e.g. MMP1, MMP3, MMP13 and ADAMTS5) (Snelling et al 2016, Yang et al 2016a, Akagi et al 2017, Khurana et al 2019.…”
Section: Links Between Dysregulation Of Circadian Rhythms and Articulmentioning
confidence: 99%